Bilateral dacryoadenitis as initial presentation of a locally aggressive and unresponsive limited form of orbital granulomatosis with polyangiitis - Lopes Caçola, Rute (BMJ Case Rep, 2016)
Limited orbital granulomatosis with polyangiitis (GPA) is uncommon and its diagnosis may be delayed, especially when isolated lacrimal involvement is the initial presentation, because clinical manifestations are non-specific and systemic diagnostic criteria are not applicable. Making an early diagnosis despite the absence of systemic progression is extremely important because in some cases the disease is locally destructive, with irreversible visual and functional loss, and it can be refractory to corticosteroids and conventional immunosuppressive drugs to induce remission. The authors report an unusual limited form of orbital GPA in a 35-year-old woman presenting with bilateral dacryoadenitis, evolving later to locally aggressive bilateral orbital pseudotumour leading to proptosis, extraocular myositis, diplopia and medial deviation of the nasal septum. She had never had systemic manifestations but her disease was persistently active and unresponsive to corticosteroids and immunosuppressors. The aim of this paper is to provide further evidence of aggressive and refractory limited forms of GPA.